The Perception of Road Users on Flyover Development Impact: A Case of Jalan RE Martadinata Bogor - Syarif, Danisy Ardanil; Rifai, Andri Irfan; Handayani, Susanty (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The high number of vehicles and the position of the railway line, which is on the same level as the road, can cause congestion. One of the sources of traffic jam locations in Bogor is on Jalan Re. Martadinata. The purpose of this research is to analyze the perceptions of road users on the Martadinata Bogor Flyover. The data collection method was carried out by distributing online questionnaires using a platform, Gform, containing seven related parameters before and after the construction of the flyover. The results of the respondents' answers were processed using the Microsoft Excel application and presented as a spider chart. In the results of the respondent's assessment, all parameters experienced an increase. Three parameters have the highest gap values, and road users and respondents feel the increase, including traffic density, accessibility, and comfort for road users. In addition, there are three parameters with the lowest Gap values, including road conditions, environmental conditions, and road components